Analysis of environment state in technogenic region and its threat to public health - Grishenko S.V.; Grishenko I.I.; Ohotnikova M.V.; Mustafina A.O.; Kudimov P.V.; Mustafin T.A. (Medičnì Perspektivi)
The purpose of the research is to give a complex hygienic evaluation of environment state in Donetsk region and to determine the degree of their potential danger to population health. It includes air pollution, water contamination, state of soil. Nearly 43000 samples of air, 32000 drinking water samples and 4500 soil samples were analyzed. Regions with the highest rate of environmental pollution were defined. It was found that the main sources of environment pollution in Donetsk region are ferrous and nonferrous metallurgy enterprises, power, coal, building industry and transport. All other sources ac¬count for only 5-10% of total emissions. Level of harmful technogenic pressing on population’s health was determined.